Nitric oxide-mediated bystander signal transduction induced by heavy-ion microbeam irradiation. (July 2015) - Tomita, Masanori; Matsumoto, Hideki; Funayama, Tomoo; Yokota, Yuichiro; Otsuka, Kensuke; Maeda, Munetoshi; Kobayashi, Yasuhiko
Abstract: In general, a radiation-induced bystander response is known to be a cellular response induced in non-irradiated cells after receiving bystander signaling factors released from directly irradiated cells within a cell population. Bystander responses induced by high-linear energy transfer (LET) heavy ions at low fluence are an important health problem for astronauts in space. Bystander responses are mediated via physical cell–cell contact, such as gap-junction intercellular communication (GJIC) and/or diffusive factors released into the medium in cell culture conditions. Nitric oxide (NO) is a well-known major initiator/mediator of intercellular signaling within culture medium during bystander responses. In this study, we investigated the NO-mediated bystander signal transduction induced by high-LET argon (Ar)-ion microbeam irradiation of normal human fibroblasts. Foci formation by DNA double-strand break repair proteins was induced in non-irradiated cells, which were co-cultured with those irradiated by high-LET Ar-ion microbeams in the same culture plate. Foci formation was suppressed significantly by pretreatment with an NO scavenger. Furthermore, NO-mediated reproductive cell death was also induced in bystander cells. Phosphorylation of NF- κ B and Akt were induced during NO-mediated bystander signaling in the irradiated and bystander cells. However, the activation of these proteins depended on the incubation time after irradiation. The accumulation of cyclooxygenase-2 (COX-2), a downstream target of NO and NF- κ B, was observed in the bystander cells 6 h after irradiation but not in the directly irradiated cells. Our findings suggest that Akt- and NF- κ B-dependent signaling pathways involving COX-2 play important roles in NO-mediated high-LET heavy-ion-induced bystander responses. In addition, COX-2 may be used as a molecular marker of high-LET heavy-ion-induced bystander cells to distinguish them from directly irradiated cells, although this may depend on the time after irradiation.